Analisa Pengendalian Persediaan Material Aluminium Ingot Menggunakan Metode Continuous Review System (Q) dan Periodic Review System (P) di PT XYZ - Zulfiqa Irfidianis Ifada; Dwi Sukma Donoriyanto (Ekonomis: Journal of Economics and Business, 2023)
The purpose of material inventory control is to ensure that needs are met accurately and at an affordable cost. However, there is currently no precise method for regulating the supply of aluminum Ingot materials in enterprises. Companies currently face difficulties in controlling inventories because they have to adjust to fluctuations in unstable market demand. This results in inventory build-up when product demand decreases and inventory shortages when demand increases. This study aims to find an inventory control model that can determine the number of orders, order time, and safety inventory levels with the aim of minimizing total costs.. After analysis and calculation, the total cost of inventory model Q is Rp. 197.114.834.539, - per year with an optimal booking quantity of 422 tons, a return booking point of 558.33 tons, a safety stock value of 143.27 tons. Meanwhile, the total cost of inventory model P is Rp. 197,341,385,235, - per year with a period between orders of 0.078 years, the optimum inventory value of 1003.23 tons, safety stock value of 200.949 tons. The results showed that the inventory model Continuous Review System (Q) can produce the most minimum inventory costs.